Cultura de calidad en el sector hotelero de la ciudad de Babahoyo - Paredes Garces, Odalys Nayeli (2023)
The purpose of this case study is to answer the question: What is the culture of quality in the services offered by the hotel sector in the city of Babahoyo? with the main objective of determining the existence of quality culture in the hotel sector of the city of Babahoyo through descriptive research, with a mixed approach, by applying interviews to owners and employees with 17 open questions related to the 3 dimensions of the HOTELQUAL model (staff, facilities and organization), in the same way the survey was applied to clients in the hotel sector, selecting 20 guests according to a type of convenience sampling, using the Likert scale of 1-5 in order to evaluate their perception, to finally compare satisfaction levels with the perspectives of employees and owners. It was obtained as a result of the customer's perception that 70% of the guests surveyed agree with the size of the staff, in terms of the dimensions of facilities and organization, around 60% disagree on aspects such as equipment, cleanliness. of common areas, room comfort, problem resolution and compliance with the conditions agreed in advance. According to the perception of the hotel owners and employees, they mention that they strongly agree with the existing quality culture, so when making the comparison with the opinion of the guests, notable differences were found; in short, a difference is evident. very poor-quality culture in the hotel sector of the city of Babahoyo, which allowed some recommendations to be made to improve the services offered.